2008
DOI: 10.5194/bg-5-339-2008
|View full text |Cite
|
Sign up to set email alerts
|

Input and output of dissolved organic and inorganic nitrogen in subtropical forests of South China under high air pollution

Abstract: Abstract. The nitrogen (N) emissions to the atmosphere and N deposition to forest ecosystems are increasing rapidly in Southeast Asia, but little is known about the fates and effects of elevated N deposition in forest ecosystems in this warm and humid region. Here we report the concentrations and fluxes of dissolved inorganic (DIN) and organic N (DON) in precipitation, throughfall, surface runoff and soil solution for three subtropical forests in a region of South China under high air pollution over two years … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
141
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 46 publications
8
141
6
Order By: Relevance
“…76 The total amount of 21.6 kg N ha −1 yr −1 , sequestrated in these three aboveground pools, is sufficient to explain the observed 21 kg N ha −1 yr −1 retained above the upper 20 cm soil through precipitation inputs. 81 Similarly, in the secondary forest, N accumulation in plant biomass and litter layer was probably higher than in the pine forest, due to higher litter production and higher foliar N concentration, 77 and might as well account for the 28 kg N ha −1 yr −1 retained in this forest. 81 It is also suggested that the balance between N supply and biological N demand generally controls leaching of NO 3 − and cations.…”
Section: Characteristics Of Soil Buffering Capacity In Tropicalmentioning
confidence: 93%
See 1 more Smart Citation
“…76 The total amount of 21.6 kg N ha −1 yr −1 , sequestrated in these three aboveground pools, is sufficient to explain the observed 21 kg N ha −1 yr −1 retained above the upper 20 cm soil through precipitation inputs. 81 Similarly, in the secondary forest, N accumulation in plant biomass and litter layer was probably higher than in the pine forest, due to higher litter production and higher foliar N concentration, 77 and might as well account for the 28 kg N ha −1 yr −1 retained in this forest. 81 It is also suggested that the balance between N supply and biological N demand generally controls leaching of NO 3 − and cations.…”
Section: Characteristics Of Soil Buffering Capacity In Tropicalmentioning
confidence: 93%
“…81 Similarly, in the secondary forest, N accumulation in plant biomass and litter layer was probably higher than in the pine forest, due to higher litter production and higher foliar N concentration, 77 and might as well account for the 28 kg N ha −1 yr −1 retained in this forest. 81 It is also suggested that the balance between N supply and biological N demand generally controls leaching of NO 3 − and cations. 82 Therefore, high plant demand for nutrients in the planted and secondary forests could be the main reason for slowing the rate of leaching loss of both NO 3 − and base cations and subsequently soil acidification.…”
Section: Characteristics Of Soil Buffering Capacity In Tropicalmentioning
confidence: 93%
“…The humid subtropical forests are considered to be N-rich compared with the boreal and temperate forests, and respond differently to N enrichment [22]. Exogenous N inputs to the subtropical forests can significantly decrease soil CH 4 uptake [21,23] and increase N loss via NO 3 À À N leaching [24], as well as via gaseous N emission (N 2 O, NO, and N 2 ) [25,26]. Experimental N deposition increases [27,28], decreases [29,30] or does not change [31e34] soil AOA abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospherically deposited N represents a new N input to terrestrial ecosystems and may enhance carbon dioxide sequestration, potentially reducing some global climate impacts (3). On the other hand, long-term N deposition could result in N saturation and increased nitrate (NO 3 − ) losses to leaching and denitrification (4,5), pathways that have different consequences for the Earth system, including consequences on climate, biodiversity, and water and air quality for human health (6). Thus, in the context of global climate and other biogeochemical changes, it is critically important to understand terrestrial N balances and their responses to anthropogenic N inputs.…”
mentioning
confidence: 99%